Flood mapping of Sungai Skudai using infoworks RS - Goodarzi, Mohsen Salarpour (2010)
Flooding is a natural part of a river's life cycle but it is a major disaster affecting many regions around the world, year after year. Malaysia is among the countries that faces potential flooding problems due to rapid development, improper river systems and climate change. The Skudai river basin covers an area of 293.7 km2 in the south-western part of Johor. The Skudai River has come under the spotlight due to its potential impacts on nearby future development projects. Based on recorded data from previous flooding events, hydrological and hydraulic analyses needed to be done. The objectives of this study are to evaluate a hydraulic analysis for flood mapping at Skudai River basin using InfoWorks RS software and produce a flood map of Skudai River before comparing the results with the results obtained using XP SWMM software. One hundred and forty cross-sections have been used to model the Skudai River. The manning coefficient values of 0.03 and 0.05 have been chosen to model the river after calibration. Results from the hydrodynamic modeling indicated water surface profiles that showed river bank overflows along with some of the hydrodynamic parameters such as flow, velocity and flood extent map for various ARIs along the Skudai River. Eighteen locations will be effected by flood disaster based on 100 ARI at Skudai River. The flood map that was generated with this model showed good comparison with the observed flood prone area map published by the DID. The water levels from InfoWorks at various ARI are approximately ninety percent similar to the results obtained from XPSWMM simulation. Thus InfoWorks RS-2D is recommended for evaluation of flood disasters as well as their impact to infrastructures and villages along the banks of the Skudai River.